ENDOFIT Taxus sumatrana (Miquel) de Laubenfels DAN POTENSINYA DALAM MEMPRODUKSI SENYAWA BIOAKTIF SEBAGAI SUMBER ANTIOKSIDAN - Sukiman, Harmastini (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Taxus sumatrana (Miquel) de Laubenfels is known as an endanger forest tree species grown at Kerinci National Park in Jambi,Indonesia. This plant was known potential on producing taxol. Taxol is a bioactive compound, could be used as antibacterial agent and recently confirmed to cure cancer cells. For the first time in 1960, Arthur Barclay found the taxol compound from Taxus sp.(pacific yew). However to isolate the bioactive compound, huge amount of tree biomass is needed. Research on endophytes microbes which are isolated from inner tissue of Taxus sp. declared that those microbes have potential on producing antioxidant agent for drug discovery. Isolation and conservation of endophytes and selecting its potential is promising the novel of finding new drug that may be effective for treating the newly developing diseases in human. Fifteen isolates of Taxus endophytes have been successfully studied on their ability on producing antioxidant. The results showed that endophytes fungus isolates TsC-17, isolated from Taxus sumatrana grown in Cibodas Botanical Gardens-LIPI, could produce extracellular bioactive compound which performed activity of suppressing free radical, is significantly better compared to intracellular bioactive compound eventhough it is not as high as in vitamin C. The activity of suppressing free radical resulted from bioactive compound of endophyte fungus isolates TsC-17 was 20% for intracellular bioactive compound, while it was 60% for extracellular bioactive compound and 90% for vitamin C.